Assessing the effectiveness of climate finance in promoting a just transition : a case study of Siyathemba Local Municipality in the Northern Cape, South Africa - Murray, Noëleen (University of Pretoria, 2023)
Dissertation (MSocSci (Development Studies))--University of Pretoria, 2022.